Corporate Governance, Risk-taking and Efficiency of Islamic Banks: Comparative Study Between Pakistan and Malaysia - Qaiser Abbas (SEISENSE Business Review)
Purpose: This study aims to compare the governance, risk-taking, and efficiency of pure Islamic Banks between Pakistan and Malaysia.